Factors influencing purchase intention of organic meat among consumers in Klang Valley, Malaysia - Wong, S. S.; Mat Said, Aini (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Multitude of factors such as concern for use of growth hormones, chemical additives in feed, animal welfare, human health issues and environmental impacts have led to the steady increase in the consumption of organic meat worldwide. The purpose of the study was to investigate the factors that influence the purchase intention towards organic meat based on the Theory of Planned Behavior (TPB) and organic meat choice motives. The influence of attitude, subjective norm, perceived behavioral control, safety, meat characteristic, health concern and price on the intention to purchase organic meat was analyzed. The study utilized cross-sectional research design using survey method. A total of 400 consumers responded to the survey using mall-intercept, with both genders equally represented and had an average age of 35 years. Results showed that the respondents seemed to be very concern about food safety (m=4.06) and meat characteristics (m=4.04) as compared to health (m=3.70) and price (m=3.36) was not a strong motivating factor (m=3.35). The level of attitude towards organic meat, subjective norm and perceived behavioral control was at moderate level. The findings showed that perceived behavioral control and personal norm towards organic meat of TPB and price and meat characteristic of the choice motives could explain 66.4 percent of the variance in the intention to purchase organic meat. As intention to purchase is an important indicator of future organic meat consumption, policy makers and marketers may draw on these results when attempting to promote and enhance acceptance of organic meat among the consumers.